The Comparison of Measuring Tear Film Break-up Time Using Conventional Slit Lamp Biomicroscopy and Anterior Segment Digital Imaging - Abdullah, Noor Afuza; Ithnin, Mohd. Hafidz; Hilmi, Mohd Radzi (Management Science University (MSU), 2019)
The stability of tear film can be measured by tear film break-up time (TFBUT). To date, the comparison value of TFBUT between slit lamp with stopwatch, which is conventional method and anterior segment digital imaging (ASDI) is under explored. The aim of this study was to compare TFBUT value between the conventional method and the ASDI utilizing iPhone 6s® video recorder. A total of 20 normal and healthy participants with 40 eyes were involved in this study. Right and left eyes from an individual were considered separately. Three measurements of TFBUT were taken from each methods and average were calculated and recorded. Mann Whitney U test was used to analyze the data and it was found that the median of the TFBUT measurement from the conventional method (2.16 seconds) was higher than the median from the ASDI (2.00 seconds). The comparison between two methods was not significant (p > 0.05). In conclusion, this study suggested that both methods could not give different result in the assessment of TFBUT.